MAKNA SIMBOL PADA RUMAH ADAT ETNIK BATAK TOBA (RUMA BOLON) DI KABUPATEN SAMOSIR - Naibaho, Marzuki; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Ruma Bolon is a traditional house of Batak Toba that is full of symbols and meanings, used by Batak Toba ethnic community as a guideline for life, ideals and hope. In Batak Toba ethnic houses (Ruma Bolon) There are aspects of symbols that have certain meanings represented by the form of houses, materials used to make houses, the arrangement of space on the house (cosmology), and ornaments carved art Batak Toba Ethnic House (Gorga). This research aims to determine the meaning of symbols in Batak Toba ethnic house, as well as to know the shift or change in the traditional house of Batak Toba ethnic in Samosir Regency  This research uses qualitative research methods with a symbolic interaction approach. This research informant is a figure of ethnic Batak Toba culture, indigenous people, the caretaker of Batak Toba ethnic house in Samosir Regency, and the community that occupies the traditional house as a home of residence chosen by the technique of Purposive. The data collection techniques undertaken are through observation, interviews, and documentation. The data analysis technique used is the interactive analysis model by Miles and Huberman.            The results of this study showed that the meaning of symbols in Batak Toba ethnic house in Samosir Regency can be seen through the form of the house, the material used to make the house, the arrangement of space on the house, and ornaments art carving (Gorga) at the traditional Batak ethnic house Toba. The shift in Batak Toba ethnic house in Samosir Regency can be seen from two aspects, namely the physical aspect of the building and the social aspect of tradition or ceremony in building a house, shifting to the physical aspects of the house include shifting to the form of Traditional Batak Toba ethnic house becomes modern, Ruma Epper, a shift in the material used in Batak Toba ethnic houses from traditional to modern, as well as a shift in carved art ornaments (Gorga) from carving into relief . The shift from the social aspect is a shift in tradition or ceremony in the construction of the Batak Toba ethnic House (Ruma Bolon) in Samosir Regency which previously existed a variety of traditional traditions or ceremonies used to build houses, but At this time, the traditional traditions or ceremonies are no longer found. Keywords: Meaning of symbol, Symbolic Interaction Ruma Bolon, Batak Toba